Reconstruction of the orbital wall using superior orbital rim osteotomy in a patient with a superior orbital wall fracture - Jae Jin Heo; Ji-Hun Chong; Jeong Joon Han; Seunggon Jung; Min-Suk Kook; Hee-Kyun Oh; Hong-Ju Park (SpringerOpen, 2018)
Abstract Background Fractures of the orbital wall are mainly caused by traffic accidents, assaults, and falls and generally occur in men aged between 20 and 40 years. Complications that may occur after an orbital fracture include diplopia and decreased visual acuity due to changes in orbital volume, ocular depression due to changes in orbital floor height, and exophthalmos. If surgery is delayed too long, tissue adhesion will occur, making it difficult to improve ophthalmologic symptoms. Thus, early diagnosis and treatment are important. Fractures of the superior orbital wall are often accompanied by skull fractures. Most of these patients are unable to perform an early ocular evaluation due to neurosurgery and treatment. These patients are more likely to show tissue adhesion, making it difficult to properly dissect the tissue for wall reconstruction during surgery. Case presentation This report details a case of superior orbital wall reconstruction using superior orbital rim osteotomy in a patient with a superior orbital wall fracture involving severe tissue adhesion. Three months after reconstruction, there were no significant complications. Conclusion In a patient with a superior orbital wall fracture, our procedure is helpful in securing the visual field and in delamination of the surrounding tissue.